Resposta do feijoeiro (cv. BRS-MG Talismã) a doses de nitrogênio e fósforo - Kikuti, Hamilton (2004)
Aiming to study the effect of N and P2O5 doses on common bean cv. BRS-MG Talismã, four field experiments were set (winter-spring 2000, spring-summer 2000/2001 and 2001/2002 and winter-spring 2002) in a typical dark red latossol at the experimental area of Departmento de Agricultura of Universidade Federal de Lavras (UFLA), Lavras-MG, Brasil. The experimental design was randomized blocks with three replications and 4x4 factorial scheme using four phosphorus doses (0, 100, 200 and 300 kg.ha -1 of P2O5, triple superphosphate source) and four doses of N (0, 70, 140 and 210 kg.ha -1 of N, urea source, split in two: the first ½ at sowing and the other ½ as side dressing at the beginning of the V4 stage of common bean cycle). By the time of the full flowering process, the sampled plants were separated in leaves and beanstalk for the macro and micronutrients content determination. At harvest, it was determined the beginning and the final standards and also the grains yield. For the economical studies of the effects that showed to be significative, the effective cost was estimated, the crude profit and the crude margin given in each situation. Enhanced N doses resulted in lowering the plants population and increasing P doses decrease N effect. The grain yield rose in the square way with the increasing of N dose, reaching peaks of maximum productivity that changed with the crop. The yield response to P2O5 was linear or quadratic and also changed from crop to crop. Those recommended N and P2O5 doses calculated based on the 90% maximum productivity were higher to those officially recommended for Minas Gerais. The N and P2O5 P2O5 applying even in higher doses did not result in higher changes among the nutrients levels from aerial parts and kept close to those said to be good bands. Increasing N in the fertilization rose a little the leaves levels of N, P, K, Mg, Cu, Zn and Mn, the branches levels of N, K, Mg and Cu and the levels of N, K, B, Cu and Mn in the flowers. With the increasing of P doses there were little elevation on B in tre leaves and in the flowers. The levels of S and of K and Zn in the common bean’s flowers decreased with the increasing of N and P2O5 doses, respectively. In most of the analysed situations, the crude margin gained with bean had rose in a square way when N or P2O5 doses were increased. These N and P2O5 doses related to points of maximum crude margin overcame those calculated doses by the 90% criteria of maximum yield. Putting analysis with differenciated prices showed to be efficient and realed that to sell the product by the lowest price of the season resulted in a negative crude margin, while, the highest season price always resulted in positive crude margin.